LOGISTIC REGRESSION ANALYSIS FOR PULMONARY TUBERCULOSIS RELATED TO ENVIRONMENTAL FACTORS IN KATOBU HEALTH CENTRE: PULMONARY TUBERCULOSIS RELATED TO ENVIRONMENTAL - Fadmi, Fitri Rachmillah; Rahmawati, Rahmawati; Fitriyanti, Fitriyanti; Mulyani, Sri; Justin, Wa Ode Sitti (STIKes Mandala Waluya Kendari, 2025)
Background: Pulmonary tuberculosis is one of the infectious diseases that has infected nearly one-third of the world's population, with many facing difficulties in its control due to a significant number of patients who do not achieve a cure. This is attributed to the challenge of pinpointing the factors that could serve as the primary causes. This study aims to predict the dominant factors contributing to the occurrence of pulmonary tuberculosis. Methods: This analytical observational study applied a case-control study design. A total of 30 patients with pulmonary tuberculosis were included as the case group, and healthy individuals without clinical symptoms of pulmonary tuberculosis were put as the control group. Data analysis used the Chi-Square test and binary logistic regression. Results: The research findings indicate a significant correlation between housing density (p=0.020<0.05), ventilation (p=0.009<0.05), room humidity (p=0,.000<0.05), lighting (p=0.002<0.05), type of flooring in the house (p=0.007<0.05) and smoking habits (p-value=0.001). The results of the multiple logistic regression analysis using the backward LR method indicate that room humidity (p-value=0.001<0.05) is the dominant factor in the occurrence of pulmonary tuberculosis. Conclusion: The incidence of pulmonary tuberculosis is higher among smokers living in homes with overcrowding, inadequate humidity and lighting, and dirt or wood floors. Room humidity plays a significant role in the development of pulmonary tuberculosis. Therefore, providing education on how to maintain and pay attention to the physical condition of the home is crucial to avoid the occurrence of pulmonary tuberculosis.